Proliferation of Rous sarcoma virus-infected, but not of normal, chicken fibroblasts in oxygen-enriched environment: preliminary report. - Mitchell, R S (1976)
Both normal and Rous sarcoma virus-infected chicken fibroblasts proliferate in an incubator containing 95% air, 5% CO2. In an incubator atmosphere enriched with oxygen, however, the normal fibroblasts are maintained without proliferation, while the Rous sarcoma virus-infected fibroblasts continue to proliferate. This suggests that a respiratory function may be involved in the regulation of proliferation of normal cells, and that neoplastic cells may proliferate autonomously because of a deficiency in this regulatory function.